GREEN ACCOUNTING: A MANAGEMENT STRATEGY AND CORPORATE SOCIAL RESPONSIBILITY IMPLEMENTATION - Purnamawati, I Gusti Ayu (International Journal of Community Service Learning, 2018)
This activity aims to know the implementation of Green Accounting As Management Strategy and Form of Social Responsibility Implementation at the Village Owned Enterprises in Buleleng Regency (BUMDes). This descriptive quantitative research was carried out with the purpose of mapping the academic works published on the environmental accounting and environmental costs areas and, fundamentally, describing the type of study (creation of a model or descriptive study) and the type of strategy (case study or non-identified). The sample is the managers of BUMDes which amounted to 10 people. With the application of environmental accounting in all operational activities and directly oriented to the interests of profit, people (community) and the planet (environmental sustainability). The results show that: 90% of the level of achievement that Bumdes managers have been able to apply environmental accounting properly.